Incorporación De La Sustentabilidad En El Modelo De Negocio De Las Empresas Más Grandes De La Industria Del Cemento En México A Través De La Gestión Estratégica - Adriana Martínez Lecuona; Manuel González Pérez; Paola Selene Vera Martínez; Ivette Flores Jiménez; Ruth Flores Jiménez; Martín Badillo Maldonado (European Scientific Journal, ESJ, 2018)
In order to operationalize the concept of sustainability in the business world, organizations have to transform their mission, align the design of the complete business system and innovate their business model (Markevich, 2009). In this sense, the purpose of the work is to study the way in which two companies in the cement industry in Mexico incorporate sustainability in the strategic management of their business model. The study was carried out through the content analysis of the sustainability reports of the companies between 2015 and 2017. The results show that sustainability is incorporated through the elements included in the four stages of the business model and in all the hierarchical levels of the companies. However, there is no balanced orientation towards the three dimensions of sustainability in both companies.